Fertility-enhancing effect of oil-based contrast agents during hysterosalpingography and the variation of this effect within a 3-year follow-up period in infertile patients - Lu, Jingyuan; Qi, Dan; Xu, Wenjian (Frontiers in Medicine, 2022)
Objective: The previous study has indicated the fertility-enhancing effect of oil-based contrast agents during hysterosalpingography (HSG) in infertile patients. However, the variation of this effect with the time frame is seldom reported. The current study aimed to explore fertility improvement using oil-based contrast agents and the change of this improvement during the 3-year follow-up period in infertile patients. Methods: Infertile women who underwent HSG with oil-based contrast agents (N=500) or water-based contrast agents (N=500) were enrolled. Spontaneous pregnancy rate and time to pregnancy were assessed at month (M)1, M2, M3, M6, M12, M24, and M36 after HSG. Results: The spontaneous pregnancy rate was 79.0% in the oil-based group and 70.2% in the water-based group. The cumulative spontaneous pregnancy rate was elevated in the oil-based group compared with the water-based group (P=0.015). Fertility-enhancing effect of HSG was elevated in the oil-based group compared with the water-based group at all time points (M1 (odds ratio (OR): 1.536); M2 (OR: 1.455); M3 (OR: 1.494); M6 (OR: 1.356); M9 (OR: 1.288); M12 (OR: 1.249); M24 (OR: 1.131); M36 (OR: 1.125). While this superiority of the fertility-enhancing effect of HSG in the oil-based group (vs. the water-based group) decreased with the time frame. Similar findings were also observed based on the physiological cycles. Conclusion: The HSG procedure with oil-based contrast agents shows a fertility-enhancing effect compared to water-based contrast agents. This improvement could last at least one year while dropping to the normal level within the subsequent two years.